Analisis Volume Sedimen Terhadap Pendangkalan Di Dalam Saluran Primer Jaringan Irigasi (Studi Kasus: D.I. Cipicung Subang) - Deny Ernawan (Departement of Civil Engineering, Universitas Winaya Mukti, 2023)
Research conducted in the primary canal of D.I Cipicung, Subang Regency, experienced damage to the irrigation network. Damage to the D.I Cipicung irrigation canal network in the primary canal, so that research is needed to find out how much silting volume is caused by sediment deposition in the irrigation canal. The method in this study uses a mathematical method to determine the volume of sediment deposition in the channel. The results show that the volume of sediment in the primary canal in the Cipicung D.I irrigation network is Vq Primary = 16.24 m3 (difference in depth 0.64 m) or 0.16% of the length per section 50.5 m of the total length of the primary canal 300 m and the change in the cross section of the primary channel is A = 1.25 m2 or 27.11%. So that the results of these calculations, it is necessary to resolve by repairing the right side of the canal lining with construction, the entrance channel from the river to the primary canal needs to be built a gate, dredging of sediment is required in the primary canal, and maintenance is required so that the canal is routinely once a week or once a month so that the strong channel is not quickly damaged.